HUBUNGAN KEJADIAN KURANG ENERGI KRONIS (KEK) DENGAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER I DI PUSKESMAS MANTRIJERON TAHUN 2011 - Huriyah, Huriyah; Tyastuti, Siti; Suherni, Suherni (Jurnal Kesehatan Ibu dan Anak, 2013)
Data Family Health Directorate indicate that 40% of the causes of maternal deaths are hemorrhage. The risk of bleeding is increased when pregnant women suffer from anemia. Greatest predisposing factors is nutritional deficiency anemia. Nutritional status of pregnant women can be measured through Upper Arm Circumference (LILA). LILA < 23.5 cm reflects the pregnant women suffer from Chronic Energy Deficiency (KEK). The prevalence of chronic energy deficiency in pregnant women in Mantijeron health centers in 2011 (30.8%) is accompanied by a high prevalence rate of pregnant women with anemia (37.55%). Objective: Knowledgeable link the KEK with the incidence of anemia in trimester I pregnant women in Mantrijeron Health Center in 2011. Methods: Observational study with cross-sectional. The study population were all pregnant women registered in the register Mantijeron Health Center in 2011 as many as 245 people. Sampling technique using consecutive sampling, samples obtained as many as 146 people. Analysis using the chi square test with ? of 5%. Results: total of 29.5% of pregnant women suffer from chronic energy deficiency and 43.2% of pregnant women are anemic. There is a relationship between the incidence of KEK with the incidence of anemia in trimester I pregnant women in Mantrijeron Health Centers TM I in Mantrijeron Year 2011 (X2 count = 9.584 p-value = 0.002). The prevalence ratio of 1.748 indicates that the KEK is a risk factor for anemia. Conclusion: There is a relationship between the occurrence of the incident KEK in trimester I pregnant women with anemia in Mantrijeron in the year of 2011 and KEK is 1.748 risk factor to be anemia.